GEN Z DI DUNIA KERJA: Kepribadian dan Motivasi Jadi Penentu Produktivitas Kerja - Putri, Pramitha Kusuma (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Generation Z, born between 1997 and 2012, has grown and developed in the digital era, exhibiting distinct characteristics in terms of personality and work motivation compared to previous generations. This research aims to analyze the impact of personality and motivation on the work productivity of Generation Z in the workplace. The study employs a quantitative method with a survey approach, targeting a sample of 200 Generation Z workers employed in various companies in Palembang city. Data is collected through a questionnaire containing questions about personality, motivation, and work productivity. The results of the research indicate that personality and motivation significantly influence the work productivity of Generation Z. Open, flexible, and future-oriented personalities positively affect the work productivity of Generation Z. Specifically, an open personality encourages Generation Z to adapt more easily to changes and new situations. Intrinsic motivation, characterized by the desire to engage in activities for pleasure or satisfaction, also enhances the work productivity of Generation Z. This is because intrinsic motivation propels Generation Z to work with enthusiasm and commitment.